Narrative Literature Review: Analysis of E-Module Development of Biodiversity Material as a Student Learning Resource - Aulia, Rizkykah; Subiantoro, Agung Wijaya (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
The education system in Indonesia has undergone many changes. The change is due to various reform efforts in the world of education. E-Module can be used as an alternative teaching material for the teaching and learning process. E-Module is a teaching material that is packaged more flexibly so that it can be accessed anytime and anywhere by students. The purpose of this study is to find out the feasibility of E-Modules from various bases, both the local potential and the type of learning method. This research was conducted using the Systematic Literature Review (SLR) method. The stages of preparing research with the SLR method generally consist of 3 steps, namely the planning stage, the implementation stage, and the reporting stage. Based on these results, the E-Module from various bases is categorized as adequate and excellent in terms of effectiveness and can be developed based on student learning outcomes.ABSTRAK: Sistem Pendidikan di Indonesia telah mengalami banyak perubahan. Perubahan tersebut karena berbagai upaya pembaharuan telah dilakukan dalam dunia Pendidikan. E-Modul dapat digunakan sebagai salah satu alternatif bahan ajar untuk proses belajar mengajar. E-Modul merupakan bahan ajar yang dikemas secara lebih fleksibel sehingga dapat diakses kapanpun dan dimanapun oleh peserta didik. Tujuan dari penelitian ini adalah untuk mengatahui kelayakan E-Modul dari berbagai basis, baik berdasarkan potensi lokal hingga berdasarkan jenis metode pembelajaran. Penelitian ini dilakukan dengan menggunakan metode Systematic Literature Review (SLR). Tahapan penyusunan penelitian dengan metode SLR umumnya terdiri dari 3 langkah, yaitu: tahap perencanaan, tahap implementasi dan tahap pelaporan. Berdasarkan hasil tersebut, kalayakan E-Modul dari berbagai basis dikategorikan memadai dan sangat baik dari segi ke-efektifan dan dapat dikembangkan berdasarkan hasil belajar siswa.